Language Competence of Students of Belgrade Business Academy for Applied Studies in Learning English for Specific Purposes (Case Study) - Kažanegra Veličković, Ana Ž.; Spasić Stojković, Milica M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Growing globalization and continuous demographic changes impose the need for reviewing language programs that must follow modern trends and the needs of students that change in accordance with the requirements of the professional environment, both in the country and abroad. The development of language competencies, especially in the field of language for specific purposes, is a prerequisite for the success of a modern young man, thus giving him the opportunity to be competitive and functional both in education and in future professional activities.The theoretical part of this paper relies on the interpretations of basic postulates about learning English for General purposes and learning English for Specific Purposes, and discusses the importance of developing language competence in teaching English in the context of acquiring professional competencies of students in higher vocational education. The paper also gives an overview of the way in which all four language skills (listening, reading, writing and speaking) are developed in teaching of ELSP at Belgrade Business Academy for Applied Studies. The aim of this paper is to present the results of research concerning the needs and interests of students in higher vocational education in terms of learning ELSP, as well as to analyze students’ attitudes about which language skills should be improved in teaching of ELSP, in order to approach the development of study programs and materials properly. The authors conducted empirical research with the use of a questionnaire as a research instrument. The analysis of data collected on a sample of one hundred students of Belgrade Business Academy for Applied Studies is seen in the context of further development of the curriculum of English language for specific purposes in higher vocational education.
Keywords: language competence; language skills; English language; language for specific purposes; curriculum